The prophet king: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story tells of a ruler who is both a prophet and a leader, emphasizing his commitment to justice and faith. It illustrates how he balances his responsibilities with compassion, showing that true leadership is rooted in moral integrity and the guidance of divine principles.